SP8.1.3 Biliary tract disease and deprivation: a Scottish retrospective study. (9th August 2022) - Dick, Lachlan; Young, Jamie
Abstract: Introduction: Deprivation and poor health is a recognized association. However, the impact of deprivation on biliary disease is less understood. We aimed to determine the effect of deprivation on admission with biliary tract disease at a Scottish district general hospital. Methods: Patients admitted with biliary tract disease were included from June 2016 to June 2019. Carstairs Deprivation scores were assigned to each patient by postcode with 5 being least deprived and 1 being most deprived. Statistical analysis was used to compare patient demographics, diagnoses, and outcomes. Results: 1116 patients were included. The majority (57.4%) were in decile 4. Only 2 patients were in decile 1 and so were excluded from the analysis. When comparing from decile 5 to 2, acute cholecystitis was more likely in patients with a lower decile (19.3 vs 23.1 vs 22.2 vs 28.4%, p=<0.05) however there was no difference when comparing age (63.3 vs 61.6 vs 62 vs 63 years, p=0.337), female gender (58 vs 60.7 vs 55.7 vs 56.7%, p=0.609) or mortality (0.6 vs 1.6, 1.3 vs 0.8%, p=0.687). Conclusion: Whilst acute cholecystitis appears to be more prevalent in patients from the most deprived areas, there is no difference in demographics or outcomes when comparing them with those from the least deprived areas. Given the relatively affluent cohort in our study, future work should include a more balanced mix of patients across the deprivation spectrum.